Impact of parents’ nutritional knowledge on the nutrition and frequency of consumption of selected products in children and adolescents practicing football in a football club in Bydgoszcz, Poland - Monika Anna Ameryk; Maciej Świątkowski; Piotr Sikorski; Agnieszka Augustyniak; Małgorzata Szamocka (Journal of Education, Health and Sport, 2017)
Ameryk Monika, Świątkowski Maciej, Sikorski Piotr, Augustyniak Agnieszka, Szamocka Małgorzata. Impact of parents’ nutritional knowledge on the nutrition and frequency of consumption of selected products in children and adolescents practicing football in a football club in Bydgoszcz, Poland. Journal of Education, Health and Sport. 2016;6(11):456-472. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.179146